2023
DOI: 10.1021/acs.nanolett.2c03693
|View full text |Cite
|
Sign up to set email alerts
|

Single-Photon Source in a Topological Cavity

Abstract: The introduction of topological physics into the field of photonics has led to the development of photonic devices endowed with robustness against structural disorder. While a range of platforms have been successfully implemented demonstrating topological protection of light in the classical domain, the implementation of quantum light sources in photonic devices harnessing topologically nontrivial resonances is largely unexplored. Here, we demonstrate a single photon source based on a single semiconductor quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…[114,115] Additionally, tailoring the coupled photonic mode, the QD emission can be encoded in orbital angular momentum, [116,117] suitable for information encoding in a large basis. Within the emergent field of topology in photonics we would like to mention two works where the QD emission is released in a topological cavity [118] or topological waveguides: [119] in these approaches, information could be propagated on-chip presenting resilience against losses or defects in the material.…”
Section: A Leading Solid-state Platform: Self-assembled Semiconductor...mentioning
confidence: 99%
“…[114,115] Additionally, tailoring the coupled photonic mode, the QD emission can be encoded in orbital angular momentum, [116,117] suitable for information encoding in a large basis. Within the emergent field of topology in photonics we would like to mention two works where the QD emission is released in a topological cavity [118] or topological waveguides: [119] in these approaches, information could be propagated on-chip presenting resilience against losses or defects in the material.…”
Section: A Leading Solid-state Platform: Self-assembled Semiconductor...mentioning
confidence: 99%
“…However, these topological quantum light sources are not realized based on semiconductor quantum dots. In 2023, Jurkat J. et al demonstrated a single-photon source based on a single semiconductor QD coupled to a topologically nontrivial SSH cavity mode and provided an in-depth study of Purcell enhancement (F p = 1.8 ± 0.4) for this topological quantum light source and demonstrate its emission of nonclassical light (the second-order correlation function of the in resonant QD gives a g (2) (0) = (0.365 ± 0.006)) on demand [87]. Figure 8c shows a sketch of the structure, where the cut through the structures highlights the difference in the cavity layer thickness and, therefore, a difference in the optical confinement potential.…”
Section: Artificial-microstructure Enhanced Single Photon Emission Fr...mentioning
confidence: 99%
“…However, challenges persist in coupling single QDs to highly confined topological cavities, primarily due to the random spatial distribution of QDs during their growth process. Previous attempts to implement such configurations encountered difficulties in achieving significant enhancement of light-matter interactions, resulting in Purcell factors below 1.8 27 , 39 . Thus, the deterministic interaction between a single QD and a topological cavity is highly desirable to fully exploit the advantageous properties of topology.…”
Section: Introductionmentioning
confidence: 99%